Transforming Pedagogical Practices Through Collaborative Work - Edgar Alirio Insuasty; María Fernanda Jaime Osorio (Profile: Issues in Teachers' Professional Development)
This article reports on the first three phases (exploration, identification, and planning) of a collaborative action research study whose main objective was to transform the pedagogical practices of teachers of a Colombian school of foreign languages. A methodology of collaborative action research and techniques, such as direct observation, completion of a reflection journal, and surveys and interviews with teachers and students was employed. Findings showed that the participants managed to identify some of the major problems they faced within their pedagogical practices and to design and implement courses of action to overcome them. Upon completion, favorable perceptions about the impact of collaborative action research on the transformation of the participating English language teachers’ pedagogical practices could be evidenced.